Perlindungan Konsumen Atas Jual Beli Masker Dikirim Batu Bata Secara Online - Aldea Ilyasa Ahyar; Jeane Neltje Saly (Fakultas Hukum Universitas Tarumanagara, 2022)
e-commerce has become a transaction that is widely used and of course with the development of thesetransactions, of course there is also a need for laws that are intended to regulate consumers andbusiness actors, so that law number 8 of 1999 was issued concerning consumer protection, where thislaw is intended to provide all necessary ef orts This law explains several things, one of which concernsthe rights of consumers and business actors, then also the obligations between business actors andconsumers, Article 4 explains the rights of consumers for example in paragraph 8 that consumers havethe right to get compensation if the goods received by the consumer are not in accordance with theagreement or not properly, but these consumer rights are often not obeyed by business actors, forexample as happened in the case of buying and selling masks online, but business actors only sendboxes containing bricks, then there is also no compensation made by business actors where consumershave suf ered losses due to this matter.